2021
DOI: 10.1002/cam4.4379
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics, laboratory parameters and outcomes of COVID‐19 in cancer and non‐cancer patients from a tertiary Cancer Centre in India

Abstract: Background There is paucity of data regarding clinical characteristics, laboratory parameters and outcomes of coronavirus disease (COVID‐19) in cancer versus non‐cancer patients, particularly from India. Materials and Methods This was an observational, single‐centre, retrospective analysis of patients with laboratory‐confirmed COVID‐19 hospitalised in our institution between 22 May 2020 and 1 December 2020. We compared baseline clinical characteristics, laboratory param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…However, published data showed that tocilizumab was used in treating severe disease in patients with utmost risk of immunosuppression including hematological malignancies and post Allogenic Hematopoietic Stem Cell Transplant with favorable and safe outcome. 17,18 Similarly, its utility in cancer patients (including those who are actively receiving chemotherapy) was reported and suggests its safe administration even among neutropenic patient's subset 19,20 In clinical practice, the golden ethical advice is to observe patient's autonomy while implementing the principles beneficence and doing no harm. 21 Following discussion with the patients, balancing benefits against risks, the clinical team decided to administer Tocilizumab therapy under monitoring then salvage the critical neutropenia with G-CSF (filgrastim) to stimulate neutrophil production to safe outcome and recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, published data showed that tocilizumab was used in treating severe disease in patients with utmost risk of immunosuppression including hematological malignancies and post Allogenic Hematopoietic Stem Cell Transplant with favorable and safe outcome. 17,18 Similarly, its utility in cancer patients (including those who are actively receiving chemotherapy) was reported and suggests its safe administration even among neutropenic patient's subset 19,20 In clinical practice, the golden ethical advice is to observe patient's autonomy while implementing the principles beneficence and doing no harm. 21 Following discussion with the patients, balancing benefits against risks, the clinical team decided to administer Tocilizumab therapy under monitoring then salvage the critical neutropenia with G-CSF (filgrastim) to stimulate neutrophil production to safe outcome and recovery.…”
Section: Discussionmentioning
confidence: 99%
“…However, published data showed that tocilizumab was used in treating severe disease in patients with utmost risk of immunosuppression including hematological malignancies and post Allogenic Hematopoietic Stem Cell Transplant with favorable and safe outcome 17,18 . Similarly, its utility in cancer patients (including those who are actively receiving chemotherapy) was reported and suggests its safe administration even among neutropenic patient's subset 19,20 …”
Section: Discussionmentioning
confidence: 99%
“…A total of 42 studies (Akhtar et al 2021 ; Alpert et al 2021 ; Arslan et al 2021 ; Azarkar et al 2021 ; Baker et al 2021 ; Benelli et al 2020 ; Bennett et al 2021 ; Bernard et al 2021 ; Bhargava et al 2021 ; Borobia et al 2020 ; Pinto et al 2020 ; Chai et al 2021 ; Fu et al 2021 ; Gude-Sampedro et al 2021 ; Guo et al 2021 ; Joharatnam-Hogan et al 2020 ; Katkat et al 2021 ; Kim et al 2021 ; Kokturk et al 2021 ; Liang et al 2021 ; Sun et al 2021 ; Lunski et al 2021 ; Martinot et al 2021 ; Mirgh et al 2021 ; Miyashita et al 2020 ; Péron et al 2021 ; Poli et al 2022 ; Li et al 2020a , b ; Reddy et al 2021 ; Ricoca Peixoto et al 2020 ; Giorgi-Rossi et al 2020; Rugge et al 2020 ; Erdal et al 2021 ; Pérez-Segura et al 2021 ; Serraino et al 2021 ; Shahidsales et al 2021 ; Sorouri et al 2020 ; Stroppa et al 2020 ; Vergara et al 2021 ; Vila-Corcoles et al 2021 ; Zhang et al 2021 ; Zhou et al 2021 ) were included in the analysis to compare the mortality rates of cancer and non-cancer patients infected with SARS-CoV-2. There were a total of 557,053 participants, of whom 21,599 were cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…After a preliminary review and the elimination of duplicates, 5328 papers were screened and chosen for further evaluation. A total of 58 studies (Adejumo et al 2021 ; Akhtar et al 2021 ; Alpert et al 2021 ; Arslan et al 2021 ; Azarkar et al 2021 ; Baker et al 2021 ; Benelli et al 2020 ; Bennett et al 2021 ; Bergman et al 2021 ; Bernard et al 2021 ; Bhargava et al 2021 ; Borobia et al 2020 ; Pinto et al 2020 ; Chai et al 2021 ; Fu et al 2021 ; Chudasama et al 2021 ; Costa et al 2021 ; Duanmu et al 2020 ; Gold et al 2020 ; Görgülü et al 2020 ; Goyal et al 2020 ; Gude-Sampedro et al 2021 ; Guo et al 2021 ; Joharatnam-Hogan et al 2020 ; Katkat et al 2021 ; Kim et al 2021 ; Kokturk et al 2021 ; Liang et al 2021 ; Sun et al 2021 ; Cavanna et al 2020 ; Lunski et al 2021 ; Martinot et al 2021 ; Mirgh et al 2021 ; Miyashita et al 2020 ; Nakamura et al 2021 ; Nikpouraghdam et al 2020 ; Panda et al 2022 ; Péron et al 2021 ; Poli et al 2022 ; Li et al 2020a , b ; Reddy et al 2021 ; Regina et al 2020 ; Ricoca-Peixoto et al 2020 ; Giorgi-Rossi et al 2020 ; Rugge et al 2020 ; Erdal et al 2021 ; Sami et al 2020 ; Santorelli et al 2021 ; Pérez-Segura et al 2021 ; Serraino et al 2021 ; Shahidsales et al 2021 ; Sorouri et al 2020 ; Stroppa et al 2020 ; Tehrani et al 2021 ; Vergara et al 2021 ; Vila-Corcoles et al 20...…”
Section: Resultsunclassified
See 1 more Smart Citation